A MATLAB-based digital elevation model (DEM) data processing toolbox (MDEM). (December 2019) - Pan, Feifei; Xi, Xiaohuan; Wang, Cheng
Abstract: A MATLAB-based digital elevation model (DEM) data processing toolbox called MDEM is built upon an improved DEM data processing algorithm, known as the PDEM, for rectifying flat areas and depressions in DEM data and producing realistic patterns of flow accumulation and extracted channel networks. Compared to the original PDEM, the computation efficiency of the MDEM has been improved significantly through adding one "fill sink" step (i.e., replace all sink pixels' elevations in a depression by the lowest elevation along the boundary of the depression) prior to applying the linear interpolation to treat each depression. The MDEM has a graphical user interface (GUI), and six functions including rectifying flat areas and depressions in DEM data using the improved PDEM algorithm, calculation of flow direction, calculation of flow accumulation area, watershed delineation, extraction of channel networks, and calculation of the topographic index. All these functions are essential for computing useful topographic variables for hydrological modeling and applications.